Plastid genome comparison and phylogenetic analyses of the Chinese group of medicinal species and related taxa within Asparagus genus - Xie, Pingxuan; Wang, Tinglu; Tan, Jiawei; Fan, Linyuan; Liu, Changkun; Yan, Hanjing (Frontiers in Plant Science, 2025)
BackgroundAsparagus L. is a large genus widely distributed across the continents of the Old World. Among its members, approximately 14 species found in China are recognized as popular herbal medicines. However, accurate authentication of these medicinal species and their phylogenetic relationships with related taxa remains unresolved.MethodsTo identify simple sequence repeats (SSRs) and divergence hotspot regions appropriate for future authentication studies, as well as to infer the phylogenetic relationships among Asparagus species, we employed a plastid genome (plastome) dataset consisting of 25 Asparagus species (21 newly sequenced and four retrieved from GenBank), encompassing 12 Chinese medicinal species, for comparative and phylogenetic analyses.ResultsAll Asparagus plastomes displayed a typical quadripartite structure with sizes ranging from 155,948 bp to 157,128 bp and harbored 114 unique genes (80 protein-coding genes, 30 tRNA genes, and four rRNA genes). IRscope and Mauve analyses indicated minimal structural variation among Asparagus plastomes. We detected between 79 to 95 SSRs across the plastomes; most were located in the large single-copy (LSC) region and primarily consisted of mono-nucleotide repeat sequences (especially A and T repeats). The genus displayed mono-, di-, tri-, tetra-, penta-, and hexa-nucleotide repeats, but with variations in types and numbers among different species. Additionally, we identified 12 special SSR motifs and seven divergent hotspot regions that may serve as potential molecular markers for future identification efforts. Phylogenetic analyses yielded a robust phylogeny for Asparagus taxa, which were split into Clades I, II, and III. Notably, medicinal Asparagus species were mainly found in Clade III. Although the phylogenetic relationships of most Asparagus species aligned with previous study findings, the phylogenetic positions of A. munitus, A. subscandens, A. gobicus, and A. dauricus were newly determined.ConclusionsThe plastomes of Asparagus are largely conserved in terms of genome structure, size, gene content, and arrangement. Nevertheless, SSRs analyses revealed significant interspecific polymorphism within Asparagus. In addition, special SSR motifs and divergent hotspot regions identified from Asparagus plastomes provided reference for subsequent identification investigations. The plastome-based phylogeny provided preliminary insights into the relationships among the Chinese group of medicinal species and related taxa within Asparagus. Overall, this study offers a wealth of informative genetic resources pertinent to Asparagus, thereby enhancing our understanding of its evolution and laying a foundation for species identification, assessment of genetic population diversity, as well as the exploration and conservation of germplasm resources.